Investigation of performance reduction of PV system due to environmental dust: Indoor and real-time analysis - Lenka S.R.; Goel S.; Satpathy P.R.; Jena B.; Sharma R. (Elsevier Ltd, 2025)
This paper analyzes the effect of different types of dust on the reduction of PV systems' performance. The PV system installed on the field gives maximum output. However, in a real-time scheme, the PV system fails to generate the desired power output due to various realistic and unavoidable factors like soiling. Different dust particles accumulating on photovoltaic (PV) modules result in shadowing and reduced irradiance, impacting power production. The study investigates eight dust samples (ash, dirt, cement, brick powder, putty, wood dust, sand, and salt) in indoor and outdoor environments. It evaluates the decrease in power at solar irradiance levels of 500, 700, and 1000 W/m. The soiling experiments conducted indoors show that the maximum% reduction in power is 39.21 % in the case of Ash, while a minimum of 8.32 % in the case of red soil. The outdoor experiments suggest that red soil, sand, and brick dust can create huge power losses in the PV system, followed by ash powder, wood dust, putty dust, salt, and cement powder. The advantages of this research lie in its thorough analysis of several forms of dust and their impact on photovoltaic (PV) systems under different circumstances. Furthermore, the study emphasizes the crucial need for implementing dust control measures to maximize system performance, thereby providing insightful information for system design and maintenance procedures. The novelty of this study is to investigate the performance impact of various kinds of dust on PV systems, offering significant insights for improving system efficiency in real-world circumstances. The research enhances the reliability and applicability of its results by thoroughly assessing outdoor and indoor conditions, bridging the gap between laboratory results and practical applications. ? 2024 The Author(s)